Endoscopic transgastric retrograde cholangiopancreatography assisted by laparoscopy in a patient with gastric bypass - Blasco, Carmelo (2025)
Obesity is a global public health problem. The development of new surgical techniques and endoscopic procedures, along with the continuous advancement of instruments and equipment in the field of gastrointestinal endoscopy, allows for the management of increasingly complex cases, including complications that may arise in patients undergoing therapeutic procedures related to obesity. The approach to the biliary tract in patients previously subjected to gastrojejunal bypass for the treatment of morbid obesity is complex due to the alterations in the anatomy of the upper gastrointestinal tract, posing a challenge for the endoscopist. In these cases, a valid alternative for managing biliary pathology is transgastric endoscopic retrograde cholangiopancreatography (LA-ERCP) assisted by laparoscopy. Below, we present a case in which LA-ERCP was used to manage biliary stones in a patient with a history of gastric bypass.